Penyusunan Laporan Keuangan Pada Usaha UMKM Ralisa - Diah Indri Anggriyanti; Lisrotul Munawaroh; Cita Kesha Avrillianda; Daariin Dewi Nabiilah; Nanda Luftiah Cahya May Salva; Sri Rahayuningsih (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
Financial reports contain information about a company's finances which can be used to assess the company's performance in a certain period, so financial reports are very important for business owners because financial reports can see the financial condition of a business and carry out performance evaluations in order to advance the business. Financial reports can also be applied to MSMEs in Indonesia. However, the obstacle faced by MSMEs is regarding financial reports. Many MSMEs do not make financial reports due to a lack of knowledge in the financial sector and a lack of awareness of the importance of financial reports in running a small business. This research includes a case study approach with qualitative methods, collecting and retrieving data in this research in the form of observation, interviews and documentation. The research results show that the problem in this research is the limited human resources in preparing financial reports.